ETUDE ET MISE EN PLACE D’UN SYSTEME DE COMMUNICATION BASÉ SUR VOIP DANS UNE INSTITUTION DE L’ENSEIGNEMENT SUPERIEUR ET UNIVERSITAIRE : « CAS DE L’UNIVERSITE LIBRE DE KISANGANI » - Lisombo, Hubert Litofo (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2025)
This article explores the implementation of a VoIP communcation system at the Université Libre de Kisangani. The transition to VoIP aims to improve internal communication costs, and provide additional services to students and staff. The study includes a needs analysis, an assessment of existing infrastructures, and recommendations for successful implementation.